P3.103 New insights into circulating neisseria gonorrhoeae sequence types using non-cultured clinical specimens in british columbia, canada. (8th July 2017) - Wong, J; Martin, I; Hoang, L; Roth, D; Gilbert, M; Grennan, T
Abstract : Introduction: From 2014 to 2015, there was a 114% and 56% increase in gonorrhoea reports in females and males, respectively. Historically, culture-based Neisseria gonorrhoeae multi-antigen sequence type (NG-MAST) surveillance is over-represented by males attending STI clinics. We sought to understand trends in NG-MAST of gonorrhoea cases among females in relation to this recent increase. Methods: From Oct to Dec 2015, the first 30–40 gonorrhoea positive nucleic acid amplification test (NAAT) samples each month in BC females were characterised by NG-MAST based on the sequence of the porB and tbpB genes. Sequence type was determined using the NG-MAST website (www.ng-mast.net). These were compared against the overall prevalent strain types as routinely reported in the National Surveillance of Antimicrobial Susceptibilities of Neisseria gonorrhoeae Annual Summary 2014. Descriptive statistics were completed using Microsoft Excel. Results: Of 112 NAAT samples analysed, 35 were non-typeable. Of the remaining 77 samples, the most common sequence types identified were ST-5985 (32%), ST-7638 (21%) and ST-4637 (10%). For comparison, ST-5985, ST-7638, and ST-4637 comprised of 52%, 0%, and 0.3%, respectively, of prevalent NG-MAST sequence types from culture in BC and NAAT in 2014. ST-7638 and ST-4637 have rarely been identified in BC cultures in prior years, but have been commonly seen in neighbouring provinces. The vast majority of ST-5985 cultures from BC demonstrated a high level of resistance to tetracycline while cultures of ST-7638 and ST-4637 have been virtually all susceptible. Conclusion: A substantial number of gonorrhoea diagnoses were identified as NG-MASTs types not previously known to be circulating in BC. Whether this represents strain replacement (which may in turn contribute to increases in incidence) or is due to undersampling of females in prior years requires further study. Ongoing strain typing surveillance of both sexes, now feasible with NAAT-based NG-MAST, will help improve our understanding of the changing epidemiology of N gonorrhoeae .